Assessment of Physico-Chemical Characteristics of Dairy Effluent and the Potential for its Reuse for Irrigation - Bhatnagar, Mridula; Gupta, Suruchi (Asian Journal of Chemistry, 2010)
The quality of dairy effluent was assessed to ascertain Its suitability for irrigation. The physico-chemical nature of dairy effluent (treated and untreated) was examined in comparison to standards used for irrigation water. The effluent contained inorganic matter in the form of cations and anions. Very high values of BOD and COD indicated high organic matter.